METHODS OF USING STEM - TECHNOLOGY IN TEACHING ANATOMY AT SCHOOL - Asanbekova Ch. A.; Bekbolotova N. N.; Abdyramanova N. T. (Vestnik Issyk-Kulʹskogo universiteta)
This paper presents the importance of using STEM technologies in global education. Currently, in accordance with the new requirements of the 21st century, significant reforms have been made to the education system of our country and ways to implement them. New goals have been defined in the education system. In Kyrgyzstan, the initiatives taken to reform education in the field of STEM call for teaching STEM subjects by integrating several related subjects. STEM is an integrated learning approach in which academic scientific and technical concepts are studied in the context of reality. The purpose of this approach is to create sustainable connections between the school, society, work with the outside world, contributing to the development of STEM literacy and competitiveness in general. On the prospects for using STEM technology elements in biology lessons. Their features in the modern educational space, allowing the targeted use of these technologies in teaching anatomy at school. The main provisions of STEM technologies, ways of their implementation in modern biological education.